Enhancing Students' Speaking Skills Through Mind Mapping Technique - saepuloh, asep; Zuber; Adelia Adiningsih, Cinde; Nurhayati Halimatu Sya'diah, Siti (Universitas Terbuka, 2025)
Speaking is one of the important language skills should be mastered by students in learning English as a foreign langugage. Someone is considered proficient in foreign language because of speaking fluency. Speaking also plays a crucial role since it is the key to communicate well in the global world. This research aims to measure the use of mind mapping technique in teaching speaking Recount text. The research involved 35 students of the first year students of English Education Study Program, Faculty of Education and Teacher Training, Suryakancana University who took Speaking for general communication course. The method of this research was Classroom Action Research. The instrument consisted of mind mapping practice, speaking test, observation sheet, and interview. The data of this research was analyzed by using two data analysis methods namely quantitative and qualitative data analysis. Quantitative data analysis was used to examining and interpreting data from Mind Mapping practice and speaking test. Meanwhile, Qualitative data analysis was taken from observation and interview. The result of this action research shows the improvement of students’speaking skills, it can be seen from the number of students who passed the minimum passing score (KKM) in the midterm test was 22.87% increased to 37.14% in the first cycle, and 77.14% in the second cycle. And it was also found that the changes of students’ speaking skills are influenced by five factors, namely, interesting teaching media, attractive classroom activities, enjoyable classroom management, attractive teaching approach, appropriate strategy or technique.